The Effect Of Event Marketing And Sponsorship On Brand Awareness Of Noodle Products At PT. Indofood Sukses Makmur Tbk Bengkulu City - Della Rahmadania; Ermy Wijaya; Dennis Rydarto (Jurnal Ekonomi, Manajemen, Bisnis dan Akuntansi, 2026)
This study aims to determine the effect of event marketing and sponsorship on brand awareness of Indofood products in Bengkulu City. The research employs a quantitative approach using a survey method through a Likert-scale questionnaire distributed to Indofood consumers. Data were analyzed using multiple linear regression with the help of SPSS version 26.0. The results of the analysis indicate that event marketing and sponsorship have a positive effect on brand awareness, as shown by the regression equation Y = 5.092 + 0.394X1 + 0.494X2. The t-test results show that event marketing has a tvalue of 2.400 > ttable 1.659, and sponsorship has a tvalue of 2.961 > ttable 1.659, both indicating significant partial effects. Simultaneously, the F-test result shows an Fvalue of 856.177 > F-table 3.08 with a significance level of 0.05, meaning that both variables jointly have a significant influence. The coefficient of determination (R²) of 0.943 indicates that 94.3% of the variation in brand awareness is explained by these two variables, suggesting that Indofood’s promotional strategy is highly effective in enhancing brand recognition and image.